2019
DOI: 10.18553/jmcp.2019.25.12.1334
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of a Telepharmacist’s Recommendations During an Integrated, Interprofessional Telehealth Appointment and Their Alignment with Quality Measures

Abstract: BACKGROUND: A growing provider shortage contributes to the widening gap in significant disparities that rural communities face. To expand access to care for rural-dwelling patients with epilepsy, a national nonprofit organization initiated an integrated, interprofessional telehealth program. OBJECTIVE: To identify gaps in care based on a telepharmacist's recommendations and determine whether these recommendations aligned with Health Effectiveness Data Information Set (HEDIS) performance measures.METHODS: A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Before the pandemic, interprofessional care teams have demonstrated that telehealth has the potential to improve patient quality outcomes, 11 medication-related problems, 12 and hospital readmissions. 13 Telehealth during the pandemic, as a modality of care, was reviewed in detail by the National Committee for Quality Assurance's Taskforce on Telehealth Policy.…”
Section: Lack Of Preparedness For the Virtual Provision Of Carementioning
confidence: 99%
“…Before the pandemic, interprofessional care teams have demonstrated that telehealth has the potential to improve patient quality outcomes, 11 medication-related problems, 12 and hospital readmissions. 13 Telehealth during the pandemic, as a modality of care, was reviewed in detail by the National Committee for Quality Assurance's Taskforce on Telehealth Policy.…”
Section: Lack Of Preparedness For the Virtual Provision Of Carementioning
confidence: 99%
“…Each resident produced one regional presentation in years one through three; beginning in year four, they also delivered one national presentation. To date, three peer-reviewed papers have been published [ 14 , 15 , 16 ]; and, one is awaiting galley proofs from a peer-reviewed journal. Early feedback from residents included a lack of guidance, which was subsequently addressed by integrating an academic-based research team to provide mentorship.…”
Section: Resultsmentioning
confidence: 99%
“…11 In another example, over 300 recommendations were made by an MTM pharmacist to 86 people with epilepsy. 12 However, several challenges remain that limit the effectiveness of the respective interventions. 13 For example, less than half (24%-50%) of eligible beneficiaries complete a CMR thus limiting the scope and ability to measure MTM's effectiveness in improving patient-related outcomes.…”
Section: ■■ Resultsmentioning
confidence: 99%